Bridging the past and present: a qualitative exploration of culinary students’ engagement with dodol as cultural heritage / Hussin Khan Rahmatullah Khan ... [et al.] - Rahmatullah Khan, Hussin Khan; Johari, Noorsa Riza; Mohamed Apandi, Siti Rohimi; Mohd Fisol, Nur Nadia Maisara; Othman, Zulhan (Universiti Teknologi MARA, Sabah, 2025)
This pilot qualitative study aims to investigate the knowledge, attitude and perception of first-semester culinary students of Universiti Teknologi MARA (UiTM) Pulau Pinang towards dodol, a traditional Malaysian food of great value. Although this food is very significant, it is ironic that its authenticity and preservation are seriously challenged. Younger generation not being aware of its preparation and the lack of research on traditional foods. The purpose of this study is to explore students’ knowledge of dodol, their views on traditional food and the factors causing its decline. Semi-structured interviews were held with 15 culinary students to achieve this; their data were thematically analysed. The results showed that most students only had a little knowledge about dodol and showed mixed feelings toward traditional food, with some expressing a nostalgic appreciation of dodol as a part of their heritage, while others felt that dodol is outdated. These differences in opinion highlight a disconnection between tradition and modern culinary trends. Along with that, institutional issues are made clear by the study. Culinary programmes are unable to represent traditional foods in the curriculum. Moreover, there are time restrictions on academic programmes. Considering these findings, the study highlights the necessity for the infusion of a traditional food module in culinary training and creating an association with local food makers to provide hands-on experience to students. Enhancing the links between schools and cultural communities may improve the understanding of traditional foods and their sustainability against globalisation. This study illustrates how culinary education can connect generations in Malaysia and help pass on Malaysia’s food heritage to future generations.